Value-at-Risk Performances during the 2007-2008 Global Financial Crisis: a comparison of three Value-at-Risk models in the emerging markets of China, India and Philippines. - Li, Mi (2012)
Ever since the world economic outlook was fundamentally changed by the 2007-2008 financial crisis, risk management and reliable risk measurements have been drew much attentions. This thesis selects three Asian emerging markets, that is, China, India, Philippine, as the research targets and evaluates the performances of three different Value-at-Risk (VaR) models (the Historical Simulation, the Monte Carlo Simulation, and the Extreme Value Theory) in these three emerging markets’ stock markets during the 2007-2008 financial crisis. Three representative stock indices (Shanghai Stock Exchange Composite Index, India S&P CNX Nifty, and Philippines Stock Exchange PSEi Index) are chosen as the market indicators and four periods (pre-crisis period (2005-2006) early stage of crisis period (2007-2008), peak stage of crisis period (2008-2009) and after-crisis period (2009-2010)) are defined in this thesis. Besides, all the VaR calculations are evaluated by the Kupiec test at 95% confidence level and the results show that all the three models underestimate the true risks in the stock markets in the crisis periods but perform well in the non-crisis periods. Moreover, no direct evidence can be found to determine the best model among three VaR models.